Safety exists in the context: the role of socialization in relation to newcomer adjustment and safety based on self-determination theory - Stoa, Rosalyn, author; Fisher, Gwenith, advisor; Brazile, William, committee member; Fletcher, Keaton, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2025)
Newly hired employees in an organization (i.e., newcomers, defined here as employees who have worked in their role for less than a year) may experience adverse effects during the beginning of their job tenure, including stress, surprise, anxiety, confusion, awkwardness, and an increased risk of injury and illness. Using self-determination theory, this study investigated how socialization tactics are related to newcomer role adjustment and perceived safety knowledge. Self-determination theory explains motivation through the satisfaction of three basic needs: autonomy, competence, and relatedness, which should also be the outcome of successful socialization and explain newcomer adjustment outcomes. Participants (N = 463) in this study are new employees from 30 locations within a large, decentralized manufacturing firm. Participants completed an online survey regarding the socialization processes they experience at work, need satisfaction, perceived safety knowledge, and self-efficacy and work acceptance. Data were analyzed using higher-order structural equation modeling. Institutionalized socialization was related to all expected outcomes, and mediated by need satisfaction, newcomer knowledge, and safety climate. Results inform research and practice to advance understanding how organizational socialization processes relate to worker safety and adjustment. Results may be used to educate human resource professionals and safety managers about ways to structure new employee onboarding to increase workplace safety and improve newcomer adjustment.